Bootstrapping line defects in AdS3/CFT2 - Gabriel Bliard; Diego H. Correa; Martín Lagares; Ignacio Salazar Landea (Journal of High Energy Physics)
Abstract We study correlators of insertions along 1/2 BPS line defects in the holographic dual to type IIB string theory in AdS 3 × S 3 × T 4 with mixed Ramond-Ramond and Neveu Schwarz-Neveu Schwarz three-form flux. These defects break the symmetries of the bulk CFT2 as PSU(1, 1|2)2 × SO(4) → PSU(1, 1|2) × SU(2), defining displacement and tilt supermultiplets. We focus on the two-, three- and four-point functions of these supermultiplets, which we compute using analytic conformal bootstrap up to next-to-leading order in their strong-coupling expansion. We obtain a bootstrap result that only depends on two OPE coefficients. We perform a Witten diagram check of the bootstrap result, obtaining an holographic interpretation of the two OPE coefficients that are not constrained by the bootstrap procedure.